Quality, bioactive compounds and enzymatic metabolism of cv. Vitoria pineapple during Maturation - Ricardo de Sousa Nascimento; Silvanda de Melo Silva; Alex Sandro Bezerra de Sousa; Mariany Cruz Alves da Silva; Renato Pereira Lima; George Henrique Camêlo Guimarães; Rejane Maria Nunes Mendonça; Edileide Natália da Silva Rodrigues (Revista Ciência Agronômica)
ABSTRACT Pineapple is a non-climacteric infructescence that needs to be harvested at the highest quality, and it is crucial to determine the ideal harvest point. This work evaluates changes in quality, bioactive compounds, expression and enzymatic activity and antioxidant metabolism during maturation of cv Vitória pineapple, recently introduced in commercial orchards, in order to define the harvest point. ‘Vitória’ pineapple infructescence were harvested from commercial planting in five maturity stages and five replications: 100% green (TG), break (B), 75% green and 25% orange (GO), 25% green and 75% orange (OG), 10% green and 90% orange (PO), and 100% orange (TO). In ‘Vitória’ pineapple during maturation, color evolution was clearly shown by the color index (CI) and firmness was higher in TG, G, BP stages. Soluble solids and titratable acidity increased as a function of the maturity stages. The ascorbic acid content was higher in the TG and G, while the yellow flavonoids, PET, and carotenoids higher from OG to PO maturity stages. Antioxidant activity by ABTS•+ and DDPH radicals were higher in the PO stage. The moleculr weight of the antioxidant enzymes regardless the maturity stages was estimated at 47 kDa POD, 28 kDa SOD, and 37 kDa APX. By gel electrophoresis, the SOD, APX, and POD accumulations were higher at earlier maturity stages, whereas the activities were higher at the TO maturity stage. Altogether, the highest quality and functional properties in ‘Vitória’ pineapple, as defined by the highest contents of bioactive compounds and higher antioxidant, activity, were found mainly in the maturity stage PO, which surely value fresh consumption.